Efficacy of biocontrol agents against seed mycoflora of groundnut at different storage periods: Efficacy of biocontrol agents against seed mycoflora of groundnut at different storage periods - A SRINIVAS; B PUSHPAVATHI; B K M LAKSHMI; V SHASHIBUSHAN (Journal of Oilseeds Research, 2020)
Groundnut seeds were treated with commercial formulations of Bacillus subtilis, Pseudomonas fluorescens,Trichoderma viride and their combinations and were stored in butter paper bags along with chemical (Carbendazim 0.2%) and untreated controls. The effect of biocontrol agents on seed mycoflora was assessed by employing standard blotter method. Frequency and per cent seed infection were calculated. Seed treatment with Bacillus subtilis + Trichoderma viride was found significantly superior with least (53.78%) per cent seed infection.